DETERMINANTS OF STRUCTURAL DIMENSION OF DAILY BEHAVIOUR IN A TRADITIONAL AFRICAN CITY: A CASE STUDY OF ILORIN, NIGERIA - ADEDOKUN, Moses Olutoyin (European Journal of Geography, 2013)
This paper analyses the determinants of daily temporal behavioral pattern of residents of Ilorin, especially the length of time spent on their activities. Data were collected from 500 residents of Ilorin, each of whom completed a time budget diary over one week. Descriptive statistics were used to summarize the data while Principal Component Analysis was used to test the research hypotheses. The result shows that the activities were fixed in time and three variables: age, income and occupation were the major determinants of the time spent on the activities. The study also shows clearly that the temporal structure of activity in Ilorin is different from what obtains in Western cities where there is flexibility in the usage of time.